Analyzing spatial relationships between urban land use intensity and urban vitality at street block level: A case study of five Chinese megacities - Xia, Chang; Yeh, Anthony Gar-On; Zhang, Anqi (Landscape and urban planning, 2020)
•Spatial relationships between urban land use intensity and urban vitality were analyzed.•Global positive spatial autocorrelation and local spatial mismatches were found.•Such relationships were associated with different urban areas, land use conditions and time periods.•The overcrowded or underutilized urban spaces were revealed by the spatial mismatches. Urban sprawl in urbanizing China has resulted in a series of ecological and environmental problems. Urban planners have been committed to promoting compact development through high-density and mixed land use. However, a problem brought by such compact urban form is the mismatch between physical spaces and socio-economic activities. To date, minimal research has been conducted using spatial statistics to study this issue at the local scales. Moreover, urban night-time vitality has been consistently ignored in existing studies. In the current work, urban land use intensity was analyzed on the basis of street block density and typology, and urban daytime and night-time vitality were measured using small catering business and night-time light data, respectively. The spatial relationships between urban land use intensity and urban vitality were investigated using a local indicator of spatial association (LISA), and five megacities in China were taken as a case study to examine whether variations exist between different cities. Results showed a significant positive spatial autocorrelation between urban land use intensity and urban vitality according to global statistics. Therefore, socio-economic activities are more likely to be abundant in densely developed urban areas. However, local spatial mismatches were found in the five megacities, indicating overcrowded or underutilized urban spaces in all the cities. These relationships were associated with different urban areas (urbanized before 1995 and during 1995–2015), land use conditions (function and mixture) and time periods (day and night). The results of this work will provide a comprehensive understanding of compact city and sustainability.